Dynamic testing of masonary houses retrofitted by bamboo band meshes - Soti, R.; Sathiparan, N.; Numada, M.; Meguro, K. (My University, 2011)
The collapse of unreinforced masonry structures, which are widely distributed around the earthquake prone regions of the world, is one of the greatest causes of death in major earthquake events. This paper presents an innovative retrofitting method for masonry structures, which uses bamboo band arranged in a mesh fashion and embedded in a mortar overlay. In order to determine the effectiveness of the proposed retrofitting technique, shake table tests were conducted using retrofitted and non-retrofitted 1/4 scaled masonry houses and each house was subjected to sinusoidal ground motion inputs. Based on the experimental results, show that the retrofitted specimen exhibited good seismic performance by withstanding a more than twice input energy than non-retrofitted specimen.
Keywords: unreinforced masonry; bamboo-band mesh